2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00281
|View full text |Cite
|
Sign up to set email alerts
|

An Internal Learning Approach to Video Inpainting

Abstract: We propose a novel video inpainting algorithm that simultaneously hallucinates missing appearance and motion (optical flow) information, building upon the recent 'Deep Image Prior' (DIP) that exploits convolutional network architectures to enforce plausible texture in static images. In extending DIP to video we make two important contributions. First, we show that coherent video inpainting is possible without a priori training. We take a generative approach to inpainting based on internal (within-video) learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 44 publications
0
58
0
Order By: Relevance
“…The sequence-to-sequence cloud removal method [28] follows the 3D Encoder-Decoder architecture of [29], constituted of an encoder as well as a decoder component. Both compo-nents are arranged symmetrically in the style of U-Net [30] and linked via skip connections between paired layers.…”
Section: B Internal Learning For Sequence-to-sequence Cloud Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequence-to-sequence cloud removal method [28] follows the 3D Encoder-Decoder architecture of [29], constituted of an encoder as well as a decoder component. Both compo-nents are arranged symmetrically in the style of U-Net [30] and linked via skip connections between paired layers.…”
Section: B Internal Learning For Sequence-to-sequence Cloud Removalmentioning
confidence: 99%
“…Moreover, the point estimator receives tuples of S1 and S2 inputs, whereas the network of Fig. 8 is driven solely by S1 data (or Gaussian noise, as proposed in [33], [29]). Finally, the sequence-topoint network of Fig.…”
Section: B Internal Learning For Sequence-to-sequence Cloud Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of video-to-video synthesis (vid2vid) [1], [3] is to convert an input semantic video to an output convincing video. Generally speaking, video restoration [18]- [23], including super-resolution [24]- [31], deblurring [32]- [37], dehazing [38]- [44], blending [45], [46] and future video prediction [47]- [53] can be considered as different research directions of the video-to-video synthesis issues. A routine approach is to represent source video as consecutive frames in order, and then generate target video from the modelprocessed images according to the time sequence.…”
Section: B Video-to-video Synthesismentioning
confidence: 99%
“…Extending this problem to video brings more challenges as the inpainted content needs to be consistent across the frames of the video. Zhang et al [80] proposed a UNNP-based video inpainting algorithm that is able to generate missing appearance and motion information, while enforcing visually plausible textures. Furthermore, they showed that their proposed framework is able to ensure mutual consistency of both appearance and optical flow of the video.…”
Section: Video Inpaintingmentioning
confidence: 99%